Historical dictionary of Nepal - Shrestha, Nanda R.; Bhattarai, Keshav, 1955- (Lanham : Rowman & Littlefield, 2017)
"This second edition of Historical Dictionary of Nepal contains a chronology, an introduction, appendixes, and an extensive bibliography. The dictionary section has more than 700 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture. This book is an excellent resource for students, researchers, and anyone wanting to know more about Nepal."--Provided by publisher.
Includes bibliographical references.
Keywords: Nepal -- History -- Dictionaries; Nepal